Analysis of Profitability Determinants of Sharia Insurance Companies in Indonesia and Malaysia 2017-2022 - Ahmad, Adzkia Fataya; Widiyanti, Dwi Retno (Islamic Economics and finance in Focus, 2025)
This research aims to evaluate how factors such as firm size, liquidity, and claim ratio influence the profitability of Islamic insurance companies in Indonesia and Malaysia between 2017 and 2022. The study utilizes secondary data collected through purposive sampling, which selected 24 companies for analysis. Panel data regression was conducted using Eviews 10 software, and hypothesis testing was performed using the t-test. The findings reveal that in Malaysia, the profitability of Islamic insurance firms is significantly influenced by firm size, liquidity, and claim load ratios. In contrast, in Indonesia, only firm size has a positive effect on profitability, with liquidity and claim load ratios showing no significant impact.